2014
DOI: 10.1007/s11307-014-0762-z
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Bacteriophage Peptide Display to Tailor Pharmacokinetics of Biological Nanoparticles

Abstract: In vivo phage display can identify phage and corresponding peptides that rapidly clear the renal system. In the future, these peptides may be used to impart favorable pharmacokinetics onto a wide range of radioimaging or therapeutic macromolecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Another investigation that also studied kidney targeting in vivo found that peptide specificity could be used for the tailoring of pharmacokinetics. 378 By directing clearance toward the kidneys and away from the reticuloendothelial system, more rapid clearance could be achieved. In vivo screening has also been applied in humans for the mapping of unique zip codes lining the vasculature.…”
Section: Biotechnologymentioning
confidence: 99%
“…Another investigation that also studied kidney targeting in vivo found that peptide specificity could be used for the tailoring of pharmacokinetics. 378 By directing clearance toward the kidneys and away from the reticuloendothelial system, more rapid clearance could be achieved. In vivo screening has also been applied in humans for the mapping of unique zip codes lining the vasculature.…”
Section: Biotechnologymentioning
confidence: 99%
“…The phage display technology described here allowed us to examine polypeptides that specifically bind to tumors. It could rapidly screen bioactive peptides, proteins, receptors, and other novel or lead compounds with high stability and specificity in the body [ 15 , 16 ]. However, the phage display technology has a limited ability to detect in vivo and in vitro differences in polypeptide metabolism or differences in affinity and clearance between polypeptides and targeted proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology has produced mixed results [ 74 , 75 , 76 ]. Thus, for the past ~20 years in vivo phage display selections have been more widely utilized to select for peptides that optimally target tissues and organs within the milieu of a live animal [ 77 , 78 , 79 , 80 , 81 ]. More recently, in vivo phage selections have been performed to identify peptides with the capability of modifying biodistribution and clearance of themselves and/or larger particles [ 78 , 82 , 83 , 84 ].…”
Section: Principles Of Phage Displaymentioning
confidence: 99%